BIOSECURITY PRACTICES AND THEIR BENEFIT ON DISEASE RISK REDUCTION IN LAYER CHICKEN FARMS: A CASE STUDY OF BABAHAN VILLAGE, TABANAN REGENCY, BALI - Keirrann Arthur Paskahadi; I Made Sukada; I Ketut Suada; Romy Muhammad Dary Mufa (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Biosecurity is a fundamental protection system in poultry farming to prevent the entry and spread of diseases. This study evaluated biosecurity implementation and its role in mitigating disease risks in layer chicken farms in Babahan Village, Tabanan Regency, Bali. Using a descriptive quantitative approach, data were collected through closed-ended questionnaires and interviews with all 33 layer farmers in the village (total sampling) and analyzed via the Guttman scale. Results revealed that farmers' biosecurity knowledge was moderately adequate (66.08% affirmative responses). Implementation varied by measure: sanitation (68.5%) and traffic control (63.62%) were moderately practiced, while isolation protocols were poorly adopted (32.74%). Effective biosecurity correlated with reduced disease transmission and sustained productivity. Key influencing factors included farmers' knowledge, farm scale, infrastructure, government support, and operational habits. The study recommends enhanced biosecurity training, provision of isolation facilities and personal protective equipment (PPE), and targeted government support for small-scale farms to improve compliance.